Hybrid solar adsorption system for domestic hot water and continuous refrigeration - Sulaiman, M. Yusof; Alghoul, Mohammad; Abdul Wahab, Mahdi; Zakaria, Azmi (2005)
Single purpose solar water heating system has been commercialized and is now widely accepted. Effort has also been made to commercialize the single-purpose intermittent solar adsorption refrigeration system, but has not been well received. The combined system for water heating and refrigeration is still in the research stage. A proposed design and performance of a hybrid continuous solar adsorption system for water heating and refrigeration is described. The system comprises conventional solar flat plate collectors, a hybrid solar flat collector containing an adsorber for refrigeration and heat recovery, an adsorber bed heat exchanger, a storage tank (container) for heating and cooling of the adsorber bed, a hot water storage tank partition, a storage tank for condenser heat exchanger, a condenser, a receiver and an evaporator. In this design solar refrigeration is realized using activated carbon as adsorbent and methanol as adsorbate. When the absorbent is cooled the adsorbate in the receiver, which passes through the evaporator converts water in the evaporator into ice. For intermittent solar adsorption this process takes place at night. The use of the adsorbent in the hybrid collector and another in the adsorber bed helps maintain a continuous refrigeration cycle. The heat rejected by the adsorber beds and condenser is recovered and used to heat water for the purpose of domestic consumption. In a continuous 24-hour cycle, 16.86MJ/day of heat can be recovered from the adsorber beds and 5.3MJ/day from the condenser. In the single-purpose intermittent solar adsorption system, this heat is however wasted. The total energy input to the dual-purpose system during 24-hour operation is 61.2MJ/day and the total energy output is 50MJ/day. The latter is made up of 44.69MJ/day for hot water heating and 5.3MJ/day for ice making. The amount of ice that can be produced is 12kg/day. Based on a typical value of 0.65 for the coefficient of performance (COP) of a single purpose solar domestic hot water heater, the following COP’s are obtained: 0.41 for single-purpose solar adsorption refrigeration, 0.73 for dual-purpose solar water heater, 0.085 for dual-purpose solar adsorption refrigeration and 0.815 for dual-purpose of both solar water heater and refrigerator.